2009
DOI: 10.1177/1053815109331864
|View full text |Cite
|
Sign up to set email alerts
|

Intervention With African American Premature Infants

Abstract: This study evaluates the efficacy of an early intervention program targeting African American mothers and their premature, low birth weight infants at 3 to 4 months' corrected age from four neonatal intensive care units, 173 families are recruited (84 intervention, 89 control). The 8-session, 20-week intervention consists of a psychoeducational video, serial administrations of the Brazelton Neonatal Behavioral Assessment Scale, and maternally administered infant massage. At postintervention, intervention mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…Studies were from Australia [49,50]; England [51,52]; Germany [53]; Italy [54]; Japan [55]; Netherlands [56]; Norway [23]; and the United States [38,40,57-61]. See Table 1 for characteristics and methods of studies included in the review.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies were from Australia [49,50]; England [51,52]; Germany [53]; Italy [54]; Japan [55]; Netherlands [56]; Norway [23]; and the United States [38,40,57-61]. See Table 1 for characteristics and methods of studies included in the review.…”
Section: Methodsmentioning
confidence: 99%
“…Four studies [38,39,54,55] included only singleton births. Five studies [40,57,58,60,61] included mother-infant pairs or dyads without mention of multiple gestations. In studies that reported allocation of multiple gestations [23,53], infants from one family were assigned to the same group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, for both high and low environmental risk samples, those families participating in the interventions were not only found to display higher levels of sensitive-responsiveness but also experienced less child-related stress and considered their children to be less challenging and temperamentally easier. 8185 These findings were not consistent across studies but do allow the possibility that benefits to children may arise at later points in time. Although all these studies were based on the MITP, variations in the MITP protocols emphasized by different groups of investigators, sample differences, and the varied training levels and types of professionals implementing the interventions (e.g., nurses, occupational therapists, and physical therapists) make it difficult to find any meaningful patterns in the outcomes for combined NICU and home interventions.…”
Section: Preventive Interventionsmentioning
confidence: 78%
“…7881 Either no effects or minor effects on children’s cognitive development have been found, despite findings of improved parent sensitive-responsiveness. In fairness, however, children have not been followed for long periods of time.…”
Section: Preventive Interventionsmentioning
confidence: 99%